2006
DOI: 10.1179/174892406x160624
|View full text |Cite
|
Sign up to set email alerts
|

BN type inclusions formed in high Cr ferritic heat resistant steel

Abstract: Scanning electron microscopy observations of fractured steel rod samples were made to clarify the formation and dissolution behaviour of boron nitrides in high Cr ferritic heat resistant steels during heat treatment at high temperature. A large number of coarse size BN type inclusions of 2 to 5 mm were distributed at the bottom of the dimples. They did not dissolve during annealing at 1150uC. However, they had a tendency to begin dissolving and reducing its particle size with time at 1200uC and dissolved compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 11 publications
2
39
1
Order By: Relevance
“…al [13] shows that the two results are generally consistent with each other since the predicted B and N composition range which results in BN formation is generally comparable. However, Sakuraya et.…”
Section: Thermodynamic Calculationssupporting
confidence: 76%
See 4 more Smart Citations
“…al [13] shows that the two results are generally consistent with each other since the predicted B and N composition range which results in BN formation is generally comparable. However, Sakuraya et.…”
Section: Thermodynamic Calculationssupporting
confidence: 76%
“…The estimated area percentage based on image analysis is less than 0.002%, which means over 97% of the BN particles observed in the as-rolled condition were dissolved after the 1448 K (1175°C) / 1 hour heat treatment. The results suggest that austenitising at 1448 K (1175°C) is very effective at dissolving the BN particles formed during the rolling process, which is lower than the required temperature reported by Sakuraya et al [13]. In their work, it was reported that BN started to dissolve at 1473 K (1200°C), and that 1523 K (1250°C) resulted in complete dissolution of BN, however, the N content (480 ppm) in their steel was approximately double that in Steel B (270 ppm).…”
Section: Dissolution Of Boron Nitride As An Effect Of Heat Treatment contrasting
confidence: 44%
See 3 more Smart Citations